Medical services in municipal properties. Criteria for evaluation of tender offers - Glanowski, Grzegorz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
Local government units try to ensure better access to health care services and assignment of municipal properties for tenancy is one of the most common ways of achieving this goal. Thanks to this activity, entrepreneurs have the possibility to start providing health care services to the local population. The author introduces the provisions of law which should be applied in order to organize and carry out such a tender. Special attention was paid to the process of constructing criteria for the evaluation of offers. The choice of business partner to render medical services in municipal properties could not be a random one. The article contains much advice on how to construct criteria for the evaluation of offers in the correct way (especially from the point of view of the tender’s goals), and reviews the most commonly committed errors by the organizers of tender processes.